Contemporary Theatre in Postcolonial Malaysia: Theatre of Roots and People's Theatre Seeking Common Ground (Melayu: Jurnal Antarabangsa Dunia Melayu, 2022)
In the late twentieth century in postcolonial Malaysia, like other parts of South Asia and Southeast Asia theatre makers reviewed traditional improvised theatres for reusable material in modern drama. The search for a theatre of roots was undertaken by urban educated authors who in late colonial period had generated scripted dramatic literature influenced by western models. Modern theatre makers trained in traditional genres have experimented with adapting Malaysian dance drama forms, creating for example mak yong for the modern proscenium stage using western narratives, as with the work of Norzizi Zukafli and Zamzuriah Zahari or bangsawan in the work of Marlenny Deenerwan. A second mode of exploration is "people's theatre" which proliferated across Southeast Asia from the 1970s and borrowed stylistic aspects of indigenous genres, but took up social and political issues of the nation, risking censorship as seen in the work of the Five Arts Center and playwright Dinsman.